Human Capital Management System Improvement For Food and Beverage MSME (Study Case: Cuankie XX) - Briani Fahriah Ramadhani Purnomo (Universitas Pahlawan Tuanku Tambusai, 2026)
The marketing division of Cuankie XX, an F&B MSME in Bandung established in December 2025, faces significant human capital management challenges including unclear role definitions, absence of formal KPIs, unstructured performance evaluation, and high employee turnover. This study aims to identify the current HCM condition and determine the improvements needed in the marketing division. A qualitative case study approach was employed using deductive thematic analysis guided by the Bassi & McMurrer (2007) framework across five drivers: Leadership Practices, Employee Engagement, Knowledge Accessibility, Workforce Optimization, and Learning Capacity. Data were collected through in-depth interviews with four informants. Findings indicate that most HCM practices are only partially implemented or not implemented at all. Only supervisory skills, collaboration, knowledge-sharing systems, and innovation are fully implemented. Recommended improvements include formalizing job descriptions, establishing SMART-based KPIs, scheduling consistent weekly meetings, developing SOPs, creating career development plans, and establishing official communication channels. This study contributes to understanding HCM implementation in early-stage MSMEs.